Study of Trichoderma Spp. Application on the Incidence of Moler Disease and Shallot's Growth and Yield - Yana Mulyana; Mariana Mariana; Joko Purnomo (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2021)
Fusarium wilt disease/moler is a concern in onion cultivation. Many farmers apply chemical pesticides such as azoxystrobin and difenoconazole to control the diseases. Both of these chemical pesticides are currently exhibiting a decline in effectiveness, prompting farmers to increase the dosage and frequency of application. Recommendations for biological control, including Trichoderma spp.. This study aimed to determine the influence of application time of of Trichoderma spp. in various media types on the incidence of moler disease and shallot growth and yield. This study was conducted in Tabalong district, South Kalimantan, from February to June 2019 using a completely randomized design (CRD) factorial comprising two nested designs. The first factor was the type of media in which Trichoderma spp.. was applied, namely solid and liquid. The second factor was the application time of Trichoderma spp.. Level 1 was the application of Fusarium sp. seven days before planting and Trichoderma spp.. seven days after planting. Level 2 included the application of Trichoderma spp.. seven days before planting and Fusarium sp. simultaneously during planting. Level 3 involved the administration of Trichoderma spp.. concurrently with planting and Fusarium sp. seven days later. This investigation used one positive control (without treatment) and one negative control (shallots inoculated with Fusarium). Each experimental unit was consisted of ten plants and replicated three times. The parameters observed were the incubation period of Fusarium sp., disease incidence, number of leaves, plant height, number of cloves, and average clove weight. The study found that the application time of Trichoderma on various types of media affected the incidence of Fusarium disease, the number of leaves, and the number of shallot cloves.When compared to liquid media, the application of solid media resulted in a reduced incidence of Fusarium disease and a greater frequency of flares. The application time on solid media gave a low response to moles. As for liquid media, the lowest incidence of moler disease occurred at the seven days before planting.